2011
DOI: 10.1128/jvi.01391-10
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Infectious Bursal Disease Virus Carrying Hepatitis C Virus Epitopes

Abstract: The delivery of foreign epitopes by a replicating nonpathogenic avian infectious bursal disease virus (IBDV) was explored. The aim of the study was to identify regions in the IBDV genome that are amenable to the introduction of a sequence encoding a foreign peptide. By using a cDNA-based reverse genetics system, insertions or substitutions of sequences encoding epitope tags (FLAG, c-Myc, or hepatitis C virus epitopes) were engineered in the open reading frames of a nonstructural protein (VP5) and the capsid pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…IBDV is capable of replicating in multiple types of cells, including chicken B cells (25), CEF and DF-1 cells (37), and Vero and HEK293T cells (33). To determine if IBDV induces a CPE in DF-1 cells, we infected cells of this cell line with the Lx strain of this virus at an MOI of 10.…”
Section: Resultsmentioning
confidence: 99%
“…IBDV is capable of replicating in multiple types of cells, including chicken B cells (25), CEF and DF-1 cells (37), and Vero and HEK293T cells (33). To determine if IBDV induces a CPE in DF-1 cells, we infected cells of this cell line with the Lx strain of this virus at an MOI of 10.…”
Section: Resultsmentioning
confidence: 99%
“…Since it was already demonstrated that SIT generates strong anti-IBDV antibody response, it is our hypotheses that incorporation of COVID-19 specific epitopes into the IBDV capsid will be able to provide coronavirus specific immune responses, which will synergize with the SIT technology. Therefore, we will incorporate the genetic sequence for COVID-19's spike epitopes into the R903/78 vector and recombinant IBDV vectors carrying COVID-19 spike epitopes will be generated (Upadhyay, et al, 2011). These vectors will be evaluated for their ability to generate immune responses against COVID-19.…”
Section: Incorporation Of Covid-19 Specific Epitopes Into the Ibdv Camentioning
confidence: 99%
“…An attenuated vaccine strain of IBDV was already successfully administered to resolve infections induced by two completely different viruses, the hepatitis B (DNA) and C (RNA) viruses (HBV/HCV) in acute and decompensated chronic hepatitis patients (Csatary, et al, 1998) (Csatary, et al, 1999). Importantly, this virus is also a potential vaccine vector drug candidate, since a recombinant IBDV was previously generated that displays exogenous viral peptides from a replication competent IBDV (Upadhyay, et al, 2011). The epidemiological efficacy of a similar strategy to SIT using attenuated vaccine viruses that stimulate the production of endogenous interferon of the host had already been tested in pivotal large scale clinical trials 2 as described below.…”
Section: Introductionmentioning
confidence: 99%
“…IBDV is capable of replicating in multiple types of cells, including chicken B cells (33), CEF and DF-1 cells (34), and Vero and HEK293T cells (35). To determine if the IBDV Lx strain could replicate in HEK293T cells, we infected this cell line with the virus at an MOI of 10 and examined the viral growth with immunofluorescence antibody assay (IFA).…”
Section: Infection Of Hek293t Cells With Ibdv Inhibits Tnf-induced Exmentioning
confidence: 99%